Monstress. Volume six, The vow - Liu, Marjorie M.; Liu, Marjorie M.; Takeda, Sana (Image Comics, Inc., 2021)
"War has engulfed the Known World, and Maika Halfwolf is at its epicenter. As she and her friends grapple with the consequences of their actions, long-buried secrets and long-awaited reunions threaten to change everything. Join MARJORIE LIU and SANA TAKEDA in the newest volume of this Eisner, Hugo, Harvey, and British Fantasy Award-winning series. Plus, learn about the happier childhood days of Kippa and Maika in MONSTRESS: TALK-STORIES 1 and 2!"--Amazon.com.